PEMINANGAN/KHITBAH DAN PROBLEMATIKA YANG SERING TERJADI - Putri, Meyrara Widya; Ulfah, Fitriani; Indah, Maulia (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
The Compilation of Islamic Law provides the understanding that promiscuity is an effort towards an arranged marriage relationship between a man and a woman. One of the purposes of proposing or proposing is to strengthen the relationship between the two male and female family members. However, the fact is that this proposal does not always end in marriage. A marriage proposal that is broken off in the middle of the road without any continuation, of course, creates problems between both sides of the family, one of which is unclear status of gift giving. Therefore, there is a need for clarity regarding the status of gifts/grants and how to review Islamic law regarding the return of multiple or double gifts/grants. This research uses qualitative research methods in descriptive form. Or a type of normative legal research, namely research data sources through library literature studies in the form of reviews of book references, research articles or journals, and other reading sources. Based on the results of research that the author has analyzed regarding the status of giving gifts/grants when the proposal does not continue to marriage, the following conclusions can be drawn: generally if the desire to stop the proposal is from the man, then he has no right to withdraw the gift or gift. which he gave. On the other hand, if the woman wishes to stop the proposal, the issue of the status of the grant/gift will depend on the agreement previously agreed upon by both parties. Regarding the cancellation of sermons by women, which occurs for example in the Kuta Baro community in Aceh and the Dayak community in Katingan, giving grants/gifts that must be returned twice as much (double) is not contrary to Islamic law, because seeing that the return is double. is considered a ta'zir punishment because it is a form of broken promise (Wanprestasi) or a violation on the part of the woman of the proposal agreement to carry out the marriage.